Cambodia - Enhancing Service Delivery through Improved Resource Allocation and Institutional Reform : Integrated Fiduciary Assessment and Public Expenditure Review - World Bank (Washington, DC, 2013)
Since 1999 Cambodia has made significant headway in reforming public expenditure policy and management, yet in order to implement its development agenda, Cambodia will have to make much more progress on four principal fiscal, fiduciary, and institutional challenges. First, Cambodia will have to improve resource mobilization to ensure aggregate fiscal sustainability. Second, to reduce the fiduciary risk to public funds, the Government will have to engage in comprehensive reform o f budget execution, cash management, and public financial control systems. Third, the Government will have to rationalize public expenditure policy and management further to carry out both its Second Socioeconomic Development Plan (SEDP) and its National Poverty Reduction Strategy (NF'RS). Last, Cambodia will have need to undertake comprehensive civil service reform-focusing on pay and employment issues-in order to deliver poverty-reducing services. The following sections elaborate on these four core challenges and provide an outline of proposed solutions.